Effect of expertise level on the perceptual characteristics of gymnasts - Croix, G.; Chollet, D.; Thouvarecq, R. (The Journal of Strength and Conditioning Research, 2010)
The first aim of this study was to investigate how visual and somatosensory information influence handstand performance according to the expertise level of gymnasts. The second aim was to determine whether the general perceptual characteristics of gymnasts are linked with their handstand performances. In the first experiment, expert and nonexpert gymnasts performed a handstand on a force platform in 4 conditions: open or closed eyes on a firm or foam support. To assess the gymnasts' performance, the surface area (mm2) covered by the trajectory of the center of pressure (CoP) was recorded. The results showed that (a) experts had significantly (p < 0.05) better postural performance during the handstand than did nonexperts, whatever the visual condition, (b) nonexperts were unable to maintain the handstand without vision, whatever the support, and (c) the CoP surface was significantly greater on the foam surface than on the firm surface for both experts and nonexperts and, only for experts, whatever the visual condition. In the second experiment, the gymnasts' general perceptual characteristics (field dependence-independence) were evaluated using the rod-and-frame test (RFT). Experts were less field dependent than nonexperts, and the RFT results were positively correlated with postural performance. We thus suggest that, although they did not cope more efficiently with the somatosensory perturbation, expert gymnasts had developed a capacity to use the remaining sensory modalities efficiently when vision was removed. Also, a high level of gymnastics training may improve the ability to change the frame of reference. For the handstand, exercises alternating the use of visual and nonvisual information could be an interesting technique for trainers to improve gymnasts' performance.